Financial Literacy and Income as Economic Factors Shaping MSME Investment Choices in Yogyakarta - Namsa, Arnoldus; Rinova, Risal; Sari, Pristsin Prima (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the factors influencing investment decisions among MSME owners in Yogyakarta, focusing on financial literacy, financial behavior, and income. While financial literacy and behavior have been widely studied, research on their impact on MSME investment decisions remains limited. The study involved a sample of 136 MSME owners selected using the Hair method and simple random sampling. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression. The results indicate that financial literacy does not significantly affect investment decisions, whereas financial behavior and income have a positive influence. The better the financial behavior and the higher the income, the more likely MSME owners are to invest. Therefore, improving financial management skills and increasing income levels are crucial factors in encouraging investment decisions. These findings provide valuable insights for MSME owners and stakeholders in developing strategies to enhance investment in the MSME sector.